Compounding of MWCNTs with PS in a Twin‐Screw Extruder with Varying Process Parameters: Morphology, Interfacial Behavior, Thermal Stability, Rheology, and Volume Resistivity. Issue 1 (4th June 2012) - Sathyanarayana, Shyam; Olowojoba, Ganiu; Weiss, Patrick; Caglar, Burak; Pataki, Bernadeth; Mikonsaari, Irma; Hübner, Christof; Henning, Frank
Abstract 1, 2, 3, 5, and 7.5 wt% MWCNTs are incorporated into PS in a twin‐screw extruder at varying speeds, throughputs and extruder barrel temperatures. Increased SME at enhanced processing speeds seems to have the single largest effect in enhancing dispersion. A relative evaluation of PS/MWCNT interactions indicate an interfacial layer growth of 24% for 2 wt% MWCNT at 1100 rpm compared to 18% growth at 500 rpm. Raman analysis does not show an MWCNT peak shift but a constant increase in FWHM is observed irrespective of the MWCNT content. A significant enhancement of thermal stability occurs up to 2 wt% MWCNT loading while 1–2 wt% shows the rheological threshold. The volume resistivity decreases dramatically in a 2 wt% sample processed at 1100 rpm compared to those processed at 500 rpm.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>